Exfoliated Mesoporous 2D Covalent Organic Frameworks for High‐Rate Electrochemical Double‐Layer Capacitors. Issue 8 (16th January 2020) - Yusran, Yusran; Li, Hui; Guan, Xinyu; Li, Daohao; Tang, Lingxue; Xue, Ming; Zhuang, Zhongbin; Yan, Yushan; Valtchev, Valentin; Qiu, Shilun; Fang, Qianrong
Abstract: The electrochemical double‐layer capacitors (EDLCs) are highly demanded electrical energy storage devices due to their high power density with thousands of cycle life compared with pseudocapacitors and batteries. Herein, a series of capacitor cells composed of exfoliated mesoporous 2D covalent organic frameworks (e‐COFs) that are able to perform excellent double‐layer charge storage is reported. The selected mesoporous 2D COFs possess eclipsed AA layer‐stacking mode with 3.4 nm square‐like open channels, favorable BET surface areas (up to 1170 m 2 g −1 ), and high thermal and chemical stabilities. The COFs via the facile, scalable, and mild chemical exfoliation method are further exfoliated to produce thin‐layer structure with average thickness of about 22 nm. The e‐COF‐based capacitor cells achieve high areal capacitance (5.46 mF cm −2 at 1, 000 mV s −1 ), high gravimetric power (55 kW kg −1 ), and relatively low τ0 value (121 ms). More importantly, they perform nearly an ideal DL charge storage at high charge–discharge rate (up to 30 000 mV s −1 ) and maintain almost 100% capacitance stability even after 10 000 cycles. This study thus provides insights into the potential utilization of COF materials for EDLCs. Abstract : Exfoliated mesoporous 2D covalent organic frameworks (e‐COFs) are utilized for the contruction of electrodes for electrochemical double‐layer capacitors. The e‐COF capacitor cells perform double‐layer charge storage at a high charge–discharge rate (30 000 mV s −1 ) and exhibit low τ0 value. They achieve areal capacitance and gravimetric power that are superior to graphitic‐carbon microcapacitors and conventional capacitors and maintain 100% capacitance retention after 10 000 cycles.